Pengukuran Dosis Neutron untuk Keselamatan Pekerja Radiasi dan Masyarakat di Pusat Terapi Proton Kompak (CPTC) Menggunakan Kode Monte Carlo MCNP6.2 - Annisa Dian Kusuma; Pandji Triadyaksa; Priyono Priyono; Fajar Arianto (Physics Education Departement, Islamic State University Sulthan Thaha Saifuddin Jambi - Indonesia, 2025)
This study aims to analyze the ambient equivalent dose H*(10) of neutrons and evaluate the effectiveness of radiation shielding at the Monte Carlo-based Compact Proton Therapy Center (CPTC) facility using Monte Carlo N -Particle (MCNP6.2) software with four variations in the direction of the proton beam (0°, 90°, 180°, 270°). The simulation was conducted to determine the effect of beam orientation on neutron radiation distribution in the area around the bunker, particularly in the Treatment Control Room (TCR) and door area. The simulation results showed that the dose distribution was highly dependent on the beam direction and the geometric configuration of the CPTC facility. The highest dose value was obtained from the 270° direction, which was 733 µSv/year. However, the dose is still below the dose limit set by the Nuclear Energy Regulatory Agency (BAPETEN), which is 1 mSv/year for the public, so the CPTC facility design is considered safe against secondary neutron exposure. This research contributes to the development of physics, particularly in the application of the Monte Carlo method for radiation protection analysis, and is expected to be a development asset for proton therapy in Indonesia.